Multiple Bluish Nodules in a 20-Year-Old Female with Similar Lesions in Her Father - Punyawee Ongsri; Supenya Varothai (Case Reports in Dermatological Medicine)
Glomuvenous malformations are congenital, benign, vascular malformations classified as subtypes of glomus tumors with predominant blood vessels, usually present at birth or childhood with multiple, bluish, soft papules and nodules or plaque-like cutaneous lesions. Later present with pronounced segmental lesions, superimposed on the primary lesions, suggesting type 2 segmental mosaicism. We present a rare case of familial glomuvenous malformations, a healthy young female presented with multiple bluish papules since birth which later developed dissemination later in her adolescence. Moreover, her father also had similar skin lesions on his left lower back.